Activation of endoplasmic reticulum stress mediates oxidative stress–induced apoptosis of granulosa cells in ovaries affected by endometrioma. (23rd December 2019) - Kunitomi, Chisato; Harada, Miyuki; Takahashi, Nozomi; Azhary, Jerilee M K; Kusamoto, Akari; Nose, Emi; Oi, Nagisa; Takeuchi, Arisa; Wada-Hiraike, Osamu; Hirata, Tetsuya; Hirota, Yasushi; Koga, Kaori; et al.
Abstract: Endometriosis exerts detrimental effects on ovarian physiology and compromises follicular health. Granulosa cells from patients with endometriosis are characterized by increased apoptosis, as well as high oxidative stress. Endoplasmic reticulum (ER) stress, a local factor closely associated with oxidative stress, has emerged as a critical regulator of ovarian function. We hypothesized that ER stress is activated by high oxidative stress in granulosa cells in ovaries with endometrioma and that this mediates oxidative stress–induced apoptosis. Human granulosa-lutein cells (GLCs) from patients with endometrioma expressed high levels of mRNAs associated with the unfolded protein response (UPR). In addition, the levels of phosphorylated ER stress sensor proteins, inositol-requiring enzyme 1 (IRE1) and double-stranded RNA-activated protein kinase-like ER kinase (PERK), were elevated in granulosa cells from patients with endometrioma. Given that ER stress results in phosphorylation of ER stress sensor proteins and induces UPR factors, these findings indicate that these cells were under ER stress. H2 O2, an inducer of oxidative stress, increased expression of UPR-associated mRNAs in cultured human GLCs, and this effect was abrogated by pretreatment with tauroursodeoxycholic acid (TUDCA), an ER stress inhibitor in clinical use. Treatment with H2 O2 increased apoptosis and the activity of the pro-apoptotic factors caspase-8 and caspase-3, both of which were attenuated by TUDCA. Our findings suggest that activated ER stress induced by high oxidative stress in granulosa cells in ovaries with endometrioma mediates apoptosis of these cells, leading to ovarian dysfunction in patients with endometriosis.